A localized surface plasmon resonance-enhanced photoelectrochemical biosensing strategy for highly sensitive and scatheless cell assay under red light excitation. Issue 79 (12th September 2016) - Li, Ruyan; Yan, Rong; Bao, Jianchun; Tu, Wenwen; Dai, Zhihui
Abstract : In this work, a novel photoelectrochemical biosensing strategy was designed for cell assay under 630 nm (red light) excitation. Abstract : In this work, a novel photoelectrochemical biosensing strategy was designed for cell assay under 630 nm (red light) excitation. WS2 /Au NP nanocomposites were prepared as a photoelectrochemical biosensing substrate. The localized surface plasmon resonance effect of Au NPs tremendously improved the photoelectric conversion efficiency and enhanced the detection sensitivity.